Economic valuation of a strategy for the animal food distribution business in Costa Rica - Vindas, Gonzalo Quiros; Ramirez, Nicole Valeria Viquez; Molina, Javier Paniagua; Thompson, Johanna Solorzano (International Journal of Economics, Business and Management Studies, 2025)
The purpose of this study was to develop a strategic plan for Alimentos El Jicote, a Costa Rican company that supplies animal feed for large and small species, with the objective of optimizing decision-making and ensuring its success. The methodology included internal and external diagnostic tools, SWOT analysis, master strategy design, qualitative financial evaluation, and the implementation of the Balanced Scorecard (BSC). The results showed a positive economic performance, with an Internal Rate of Return (IRR) of 10.35%, higher than the cost of capital, and a positive Net Present Value (NPV) over a 10-year horizon. The strategy proposed was to diversify the supply of animal feed products with the best quality and at the best possible price, based on negotiations with more efficient suppliers by increasing storage capacity and the distribution network of the trade. In conclusion, although its financial situation is stable, areas for improvement in the company’s profitability, liquidity, and market were identified; thus, the practical implication of the study was based on strategic planning for adaptation to the market, facilitating decisions, maintaining competitiveness, and ensuring long-term sustainability.